Finite element analysis of rc deep beams with openings located in the mid of shear span - Nur Lyana, Ameerudeen (2014)
The research was carried out in order to study the behaviour of reinforced concrete deep beams with web openings. Openings are often provided in beam for accessibility purpose and to accommodate essential services such as power supply, ventilation system and network system access. However, the presence of openings in deep beams may lead to many problems in the beam behaviour such as reduction in the beam capacity, cause excessive cracking and deflection. Due to limited research in numerical approach, this study was performed in order to study the behaviour of reinforced concrete deep beams with web openings by validating the FEM results with the experimental study. A total of seven beams including one control beam was modelled as simply supported beams in two-dimensional analysis, using a finite element program, ATENA. In this study, the openings were placed at the mid of the shear span. The shapes and sizes of openings considered in this study were rectangular (150 x 250 mm, 200 x 250 mm, 250 x 300 mm) and circular (0150 mm, 0200 mm and 0250 mm). The beams were in a cross section of 100 mm x 500 mm and 1200 mm in length. The results considered in this study were the load-deflection curve/behaviour and the crack patterns. Increasing the size of openings resulted into a reduction in the beam capacity where it was observed that BRO1, BR02, BR03, BCO1, BCO2 and BCO3 reduces the beam capacity by 40.36%, 54.68%, 66.98%, 39.71%, 44.72% and 47.04% respectively as compared to the control beam. It was found that the use of circular opening has advantage over using rectangular opening regarding the structural strength. Rectangular openings reduces the strength about 0.65% to 19.94% greater than circular openings due to the high stress concentration at the corners of the openings. Solid control beam failed due to flexure cracks which turned to shear cracks whereas beams with openings (rectangular and circular) failed due to the shear cracks. A fair agreement on the crack patterns obtained by FEM and experimental results were observed.